Effect of project-based learning models and achievement motivation on students' short story text writing skills - Rahayu, Sri; Afnita, Afnita (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The implementation of learning short story writing skills is still oriented towards completing tasks designed by the teacher. Also, it seems conventional, so developing students' short story writing skills takes time and effort. Through this research, the authors review the effect of the project-based learning model on learning outcomes for students with high and low achievement motivation; and the interaction between the project-based learning model and achievement motivation. This research belongs to the quantitative research that applies the experimental method, involving two sample classes: class X hospitality 2 as the experimental class and class X clothing 4 as the control class. The results of the data analysis provide conclusions. First, the project-based learning model influences student learning outcomes. Second, the project-based learning model influences students' learning outcomes with high achievement motivation. Third, project-based learning model influences the learning outcomes of students with low achievement motivation. The project-based learning learning model can be used as an effective alternative learning model in improving students' short story writing skills.